Traffic Flow and Simulation at the Jalan Kebudayaan 28 (Junction of Jalan Pendidikan – Jalan Kebudayaan) in Skudai, Johor - Sabarudin, Safi Aqila; Othman, Mohd Hanifi (Recent Trends in Civil Engineering and Built Environment, 2021)
The increase in populations in Skudai, Johor Bahru causing an increase in the number of vehicles which lead to traffic congestion. There is congestion issue at Jalan Kebudayaan 28 (Junction of Jalan Pendidikan – Jalan Kebudayaan) in Skudai. This study is to evaluate the traffic parameter such as traffic volume, traffic density and traffic speed at the selected area and simulate traffic flow at the case study location based on the data obtained by using VISSIM Software (student version 2021). The manual count method was used in collecting data for 3 days with 3 sessions at a particular time. The obtained data were used to simulate the traffic flow by using VISSIM Software to determine the LOS in every session including before and after mitigation action was proposed. LOS F was obtained in every session before appropriate mitigation strategies have been proposed to improve the delay of service and traffic movement by the appropriate design traffic signal timing at the intersection such as the combination between the law of enforcement and enlarge lane shows a positive result which obtained above LOS C which in acceptable vehicle delay.